Housing Unit and Households Projection Methods in the Palestinian Territory up to‏ ‏‎2010‎ - Mahmoud Abd-Alrahman (My University, 2004)
Development planners require future estimates about households and housing units in order to create appropriate strategies for short-term and long-term services in line with the size and need of the Palestinian society. There are several projection methods for households and housing units, however, internationally applied housing units projection methods cannot be applied to the Palestinian Territory in the present time due to lack of necessary data. Households’ projections have been used to identify the number of housing units, which the Palestinian Territory will need in the coming years. In this study a future estimates concerning the number of households and housing units based on several methods of projection: such as head of households rate method and average of household size method. According to estimates, the number of housing units of the Palestinian Territory will rise from 460,418 in 1997 to 752,875 in 2005 with an increasing rate of 63.5%. Estimates also show that the number of housing units of the Palestinian Territory of 2010 will be 973,761 including 650,804 in the West Bank and 322,957 in Gaza Strip. In the light of the above mentioned results concerning housing projections, it is possible to say that the head of households rate method is the closest to reality, especially that such method has been used by a number of countries and recommended by the United Nations. The head of households rate method is also applicable to many countries including those with insufficiently developed statistics and methods of analysis. The average of household size method, which assumes a drop by 0.05 annually, showed close results to those of the internationally recommended head of households rate method.

تتطلب عملية رسم السياسات ووضع الخطط المستقبلية في الأراضي الفلسطينية في مجال إحصاءات المساكن، توفر تقديرات حول الحاجة الفلسطينية لعدد الوحدات السكنية المستقبلية خلال فترة من الزمن. تهدف هذه الدراسة إلى معرفة طرق اسقاطات المساكن والأسر المناسبة للتطبيق في الأراضي الفلسطينية، وذلك من خلال دراسة عدة طرق لإعداد اسقاطات المساكن والأسر تم اتباعها في دول العالم المختلفة، واختيار ما نستطيع استخدامه لإعداد إسقاطات المساكن والأسر في المجتمع الفلسطيني، وبما يتفق مع خصوصية المجتمع الفلسطيني من جهة، وتوفر البيانات اللازمة لاستخدام هذه الطرق من جهة أخرى. اعتمدت التقديرات التي تضمنتها هذا الدراسة على التجربة الدولية، وعلى الاسقاطات السكانية التي قام بها الجهاز المركزي للإحصاء الفلسطيني. تشير التقديرات إلى أن عدد الوحدات السكنية في الأراضي الفلسطينية سوف يرتفع من 460,418 وحدة سكنية في العام 1997، إلى حوالي 752,875 وحدة سكنية في العام 2005، أي بزيادة قدرها 63.5%. وفي العام 2010، سوف يبلغ 973,761 وحدات سكنية، ويتوزع هذا العدد حسب المنطقة إلى 650,804 وحدة سكنية في الضفة الغربية، مقابل 322,957 وحدة سكنية في قطاع غزة. وتشير النتائج والاستنتاجات إلى أن طريقة معدل رئاسة الأسر أقرب ما تكون للواقع، لا سيما ان هذه الطريقة تم استخدامها في عديد من دول العالم حيث تعتبر هذه الطريقة من الطرق التي توصي الأمم المتحدة باستخدامها، وتصلح للاستخدام في أقطار عديدة بما في ذلك تلك التي لم تتطور إحصاءاتها وطرق التحليل فيها بطريقة كافية. كما أن استخدام فرضية متوسط حجم الأسرة التي تفترض انخفاض هذا المتوسط بمعدل (0.05) فرد سنويا عما هو عليه حسب تعداد 1997 قد أظهرت نتائج قريبة من النتائج التي تم التوصل إليها باستخدام فرضية معدل الرئاسة والموصى بها دولياً.
طرق إسقاطات المساكن والأسر في الأراضي الفلسطينية حتى عام 2010‏